Isaac Watts and the Hymn Singing Revolution - Colin Harris (Miranda: Revue Pluridisciplinaire du Monde Anglophone)
Isaac Watts has often been called the “Father of English Hymnology”, being at the head of a great outpouring of hymn compositions and hymn singing during the eighteenth century. This article shows that the communal singing of English hymns actually had its origins in the royal courts of France and England but was finally achieved among the Nonconformists around the City of London. Many of the advances in composition began with the congregational singing of psalms in the sixteenth century developed through the interactions of theologians, royalty and poets in the French-speaking world. However, the communal singing of hymns began a century later as a slow painful process among the disadvantaged and excluded. Despite persecution and internal opposition, it was a network of “sectaries” of late seventeenth century England who finally implemented communal hymn singing: they were the Particular Baptists. A major inspiration was also provided by a reclusive and sensitive Anglican priest called John Mason. It was then in the early eighteenth century, with this foundation of composition and practice in place that poet, theologian, and Congregational minister, Isaac Watts (1674-1748), was able to compose and publish his works and make hymn singing available to a much wider public and consequently stimulate a new generation of hymnwriters.